QUANDO I MIGRANTI ARRIVANO IN CITTÀ - Jean Marc Fournier (Bollettino della Società Geografica Italiana, 2019)
The Conference brought together nearly 80 researchers, of whom 30 were Italian, to discuss 27 papers. Several main points emerged from this very informative, stimulating and above all necessary conference: the reception of migrants is too often presented as being a problem whereas it can also be considered as a solution; the migrant crisis interacts with the European crisis in general, and they are probably both the cause and the effect; citizens and activists have sometimes no other choice than to resist and to disobey when faced by the absurdity of certain Kafkaesque laws; the linguistic issues must be taken into account; gender and age are variables that have to be identified to understand the diversity of practices and paths followed. These points only summarise the most salient aspects and do not convey the full value of the discussions during the conference, which was able to make a contribution to our understanding of the reality of the situation.